Musculoskeletal pain characteristics associated with lower balance confidence in community-dwelling older adults. Issue 2 (June 2016) - Stubbs, Brendon; Schofield, Patricia; Patchay, Sandhi; Leveille, Suzanne
Abstract: Objective: To determine whether musculoskeletal pain (pain severity and number of chronic pain sites; single or multisite) is associated with balance confidence over and above previously established risk factors. Design: Cross-sectional study. Setting: Ten community sites (five day centres, two sheltered housing schemes and three community 'clubs') in the UK. Participants: Two hundred and eighty-nine community-dwelling older adults [response rate 72%, mean age 78 (standard deviation 8) years, 67% female] completed the study assessment. Eligibility criteria were as follows: living in the community; aged ≥60 years; able to walk ≥10 m; able to communicate in English; and no cognitive (e.g. dementia), neurological or mental health conditions. Interventions: Not applicable. Main outcome measure: Balance confidence as measured by the 16-item Activities Balance Confidence (ABC) scale (lower scores indicate less confidence). Results: One hundred and fifty participants had at least one site of chronic musculoskeletal pain (52%), and the remaining 139 (48%) participants did not report chronic musculoskeletal pain. Older people with chronic musculoskeletal pain had significantly lower scores on the ABC scale compared with those without chronic musculoskeletal pain (mean 48.3 vs 71.3, P  < 0.001). After adjustment for established risk factors, two separate hierarchical regression models demonstrated that both pain severity ( β  = −0.106, P  = 0.029) and number of chronic musculoskeletal pain sites ( β  = −0.98, P  = 0.023) were significantly associated with lower balance confidence. Conclusion: Both pain severity and number of chronic pain sites (particularly multisite pain) are associated with lower balance confidence in community-dwelling older adults. Further research is needed to target pain symptoms and balance confidence in relation to fall risk in older adults with chronic musculoskeletal pain.